Arte e Cegueira: reflexões sobre acessibilidade multissensorial de obras de arte bidimensionais - Guimarães, Viviane Alves (2024)
This article aims to present a contribution to the teaching of art to blind students enrolled in basic education. It is the result of a research with a qualitative approach, of the case study type with participant observation. This paper focuses on the development of the autonomy of blind students when in a situation of aesthetic enjoyment of two-dimensional visual works of art, as well as on increasing their creative, cognitive, sensitive and imaginative potential. It proposes reflections on the promotion of artistic experiences for blind students, in order to assist the art teacher in offering accessibility and aesthetic enjoyment for people with visual impairments. In this way, visually impaired students, enrolled in the regular education network will be able to experience the reading and contextualization of a two-dimensional work of art together with the other students in an art education class without the barriers imposed by an artistic education that prioritize vision.